Factors associated with 30-day readmission after primary total hip arthroplasty: analysis of 514455 procedures in the UK National Health Service - Ali,AM; Loeffler,MD; Aylin,P; Bottle,A (JAMA Surgery, 2017)
Importance: Thirty-day readmission to hospital after total hip arthroplasty (THA) has significant direct costs and is used as a marker of hospital performance. All-cause readmission is the only metric in current use, and risk factors for surgical readmission and those resulting in return to theater (RTT) are poorly understood. Objective: To determine whether patient-related predictors of all-cause, surgical, and RTT readmission after THA differ and which predictors are most significant. Design, Setting, and Participants: Analysis of all primary THAs recorded in the National Health Service (NHS) Hospital Episode Statistics database from 2006 to 2015. The effect of patient-related factors on 30-day readmission risk was evaluated by multilevel logistic regression analysis. The analysis comprised all acute NHS hospitals in England and all patients receiving primary THA. Main Outcomes and Measures: Thirty-day readmission rate for all-cause, surgical (defined using International Statistical Classification of Diseases and Related Health Problems, Tenth Revision primary admission diagnoses), and readmissions resulting in RTT. Results: Across all hospitals, 514455 procedures were recorded. Seventy-nine percent of patients were older than 60 years, 40.3% were men, and 59.7% were women. There were 30489 all-cause readmissions (5.9%), 16499 surgical readmissions (3.2%), and 4286 RTT readmissions (0.8%); 54.1% of readmissions were for surgical causes. Comorbidities with the highest odds ratios (ORs) of RTT included those likely to affect patient behavior: drug abuse (OR, 2.22; 95% CI, 1.34-3.67; P = .002), psychoses (OR, 1.83; 95% CI, 1.16-2.87; P = .009), dementia (OR, 1.57; 95% CI, 1.11-2.22; P = .01), and depression (OR, 1.52; 95% CI, 1.31-1.76; P < .001). Obesity had a strong independent association with RTT (OR, 1.46; 95% CI, 4.45-6.43; P < .001), with one of the highest population